Cost-Effectiveness of an Integrated Service Delivery Model : A Study on Worker Retention - Kiran Singh, (International Journal of Scientific Research in Science and Technology, 2024)
This paper examines the cost-effectiveness of an integrated service delivery model by evaluating its impact on worker retention. The Neighborhood Place (NP) model, implemented in Louisville, Kentucky, serves as the focal point for this analysis. Co-locating multiple social service providers in a single community-based location, the NP model provides an innovative approach to service delivery. The paper explores how reducing worker stress, improving job satisfaction, and decreasing turnover rates lead to significant cost savings. This research highlights the broader implications of integrated service models for workforce retention and agency efficiency.
Keywords: Integrated Service Delivery Model; Cost-Effectiveness; Worker Retention; Neighborhood Place (NP) Model; Louisville, Kentucky; Social Service Co-Location; Job Satisfaction; Employee Turnover; Workforce Retention; Agency Efficiency; Child Welfare